Anti-tumorigenic and Platinum-Sensitizing Effects of Apolipoprotein A1 and Apolipoprotein A1 Mimetic Peptides in Ovarian Cancer - Marinho, Aline T.; Lu, Haonan; Pereira, Sofia A.; Monteiro, Emília; Gabra, Hani; Recchi, Chiara (Frontiers in Pharmacology, 2019)
Objective: Apolipoprotein A1 (ApoA1) is remarkably decreased in serum and ovarian tissues of ovarian cancer patients. ApoA1 and ApoA1 mimetic peptides can sequestrate pro-inflammatory phospholipids, some of which are known to activate a variety of oncogenic pathways. Besides, more intrinsic anti-tumorigenic properties, independent from interaction with lipids, have also been described for ApoA1. We aimed to disclose the effects of ApoA1 and a mimetic peptide on the malignant phenotype of ovarian cancer cells, particularly regarding cell viability, invasiveness and platinum sensitisation. Methods: Cells viability was assessed by MTS assay. Extracellular matrix invasion was assessed by transwell and a 3D tumour spheroid invasion assays. Western blotting was performed to evaluate the effect of test compounds on intracellular pathways. Sensitisation assays were performed in vitro and in the biologically relevant in ovo chorioallantoic membrane model. Results: Both ApoA1 and the mimetic peptide, at a concentration of 100 µg/mL, were able to decrease the viability of SKOV3, CAOV3 and OVCAR3 cells (p<0.05). The peptide at this concentration did not present unspecific toxicity towards non-neoplastic ovarian cells. The peptide at this concentration was not able to affect the viability of immortalised non-neoplastic ovarian cells (p>0.05). ApoA1 decreased SKOV3 cells invasiveness at 300 µg/mL after 72h and 96h of exposure (p<0.05), while the ApoA1 mimetic peptide prevented cell invasion at 50 and 100 µg/mL (p<0.01). Treatment with 100 µg/mL of ApoA1 mimetic peptide decreased Akt phosphorylation in SKOV3 cells (p<0.01). Accordingly, treatment with increasing concentrations of the peptide sensitised SKOV3, OVCAR3 and CAOV3 cells to cisplatin. This sensitisation synergistic effect was observed both in vitro and in ovo. Conclusions: These results support the role of ApoA1 and ApoA1 mimetics as suppressors of ovarian tumorigenesis and as chemo-sensitising agents.